ANALYSIS OF THE PROCESS OF ORGANIZING AJI KUNING VILLAGE GOVERNMENT WITH A SYSTEM PERSPECTIVE GOVERNMENT ECOLOGY APPROACH - Mulka, Sry (Department of Government, FISIP, Universitas Padjadjaran, 2022)
gb777